SISTEM INFORMASI PENGAJUAN KLAIM JAMINAN PEMELIHARAAN KESEHATAN MASYARAKAT BERBASIS WEB - Adi Supriyatna (LPPM Universitas Bina Sarana Informatika, 2016)
The use of computers as the technology to impact the health of the world that such a claim onJaminan Pemeliharaan Kesehatan Masyarakat (JPKM). Once the insurance company requires theexistence of an information system that could facilitate providers in filing his claim. For that, theresearch done on the system of filing a claim on the insurance company, which until now has notbeen computerized. The system used is still done manually starting from the filing of the claims aresent via EMAIL later use in processing and submission of data to recapitulate the claim still usingMicrosoft Excel Software. Such a situation is very clear may inhibit the process of filing a claimcan result in the claim process to be delayed. The design of this information system is the bestsolution to solve the problems that exist. System development method used is the method of RapidApplication Development (RAD), which consists of four stages, namely Requierements Planning,User Design, Construction and cutover Phase. The result of this information system can facilitatethe provider to submit the data on claims and provide convenience for the insurance company,especially in the claims section to check the claim documents online. So the claim filing systemthat will be implemented are more favorable than the previous system.Keywords: Information System, JPKM, RAD.